Pengaruh Pelaksanaan Pemeriksaan Pajak Terhadap Tingkat Kepatuhan Wajib Pajak Orang Pribadi Pada Kantor Pelayanan Pajak Pratama Gorontalo - Titi Umi Kalsum Hulopi (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
The Influence of Tax Audit Implementation on the Level of Compliance of Individual Taxpayers at the Gorontalo Pratama Tax Service Office. This study aims to test and determine the influence of Tax Audit Implementation on the Level of Compliance of Individual Taxpayers at the Gorontalo Pratama Tax Service Office. The conclusion of this study is that there is an influence of tax audit implementation on the level of compliance of Individual Taxpayers at the Gorontalo Pratama Tax Service Office by 31.2% while 68.8% is influenced by other factors that are not tested. The steps that should be taken by Account Representatives and Tax Audit Officers are expected to further improve the implementation of audits in accordance with audit standards, because these audit standards can maintain the quality of audits, so that every year the compliance of Individual Taxpayers will continue to increase.